Client driven trading strategies: a practical modeling in the context of financial derivatives market. - Mohanan Potti, Aravind (Serbian Journal of Management, 2019)
Financial derivatives are widely recommended by financial advisors and brokers to hedge the investment position of their clients. But due to the heterogeneity existed between retail investor groups they are not in a position to offer more customized service to their clients.  The present study is developed on the basis of a survey conducted among 200 experts working in various broking firms. The opinions, so collected from experts were evaluated using different statistical measures in order to select some suitable strategies. Statistical tools like MANOVA, Chi-square, paired sample ‘t’ test, etc. were used to analyze the viability of the expert recommendations. Based on this empirical analysis some strategies were identified for derivative trading and a theoretical model was formulated for dealing with diversified group of retail investors.
Keywords: Role of Stakeholders; Managing Client traffic; Client Driven Business Model